INFORMATION GOVERNANCE: A FRAMEWORK FOR ENHANCING DATA INTEGRITY, COMPLIANCE, AND ACCESSIBILITY IN ACADEMIC LIBRARIES - Nandeesha L; Keshava (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Information Governance (IG) is a critical component of modern academic libraries and it is essential for academic libraries to manage digital assets effectively, ensuring data integrity, regulatory compliance, and user accessibility. This study explores the theoretical foundations of IG in academic libraries, emphasizing policies, technological infrastructure, and stakeholder collaboration. As libraries transition to digital environments, challenges such as data privacy, preservation, and resource constraints necessitate structured governance frameworks. The article proposes a four-tiered IG model strategic planning, policy development, technology integration, and continuous evaluation to optimize information management. By aligning IG with institutional objectives, libraries can enhance security, meet legal requirements, and improve service delivery. The study highlights the role of metadata standards, encryption, and AI in facilitating efficient data handling while addressing ethical and operational concerns. Ultimately, this framework supports sustainable knowledge stewardship, fostering trust and usability in academic research ecosystems. Future research should examine emerging technologies like blockchain and big data analytics to refine IG practices in academic libraries.